2020
DOI: 10.46234/ccdcw2020.074
|View full text |Cite
|
Sign up to set email alerts
|

The “1-3-7” Approach to Malaria Surveillance and Response — Henan Province, China, 2012−2018

Abstract: What is already known about this topic? The “1-3-7” approach to malaria surveillance and response was a key measure for malaria elimination in China and was first introduced into the World Health Organization (WHO) as an international guideline for malaria surveillance and response in 2018. What is added by this report? The “1-3-7” approach was well implemented in Henan Province from 2012−2018. Over this study period, a total of 1,294 malaria cases were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Cao et al reported that 100% of these cases were reported through CISDCP within 24 h, more than 99.4% of the malaria cases were verified and received epidemiological investigation within 3 days, and more than 98.3% of foci completed investigation and response within 7 days [ 20 ]. Similarly, Shanxi Province and Henan Province, which achieved zero indigenous malaria since 2012, also have a well adherence to the timelines of 1-3-7 approach [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al reported that 100% of these cases were reported through CISDCP within 24 h, more than 99.4% of the malaria cases were verified and received epidemiological investigation within 3 days, and more than 98.3% of foci completed investigation and response within 7 days [ 20 ]. Similarly, Shanxi Province and Henan Province, which achieved zero indigenous malaria since 2012, also have a well adherence to the timelines of 1-3-7 approach [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…From 2012 to 2018, only 13.14% (170/1294) of malaria cases in Henan Province in China were diagnosed within 24 h after onset. The median time from onset to diagnosis was 3 days [ 22 ]. Similarity, Feng et al reported that it took an average of 8.5 days for patients from onset to diagnosis in the China-Myanmar border region in 2013–2014 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ‘1-3-7’ approach to malaria surveillance and response was a key measure for malaria elimination in China that aims to have all cases of malaria reported within 1 day, case investigation conducted within 3 days and an in-depth investigation conducted within 7 days. 41 This approach was also introduced by WHO to be a guideline to instruct malaria control programmes worldwide, especially in countries or regions where malaria is close to elimination. 42 It was demonstrated that the malaria burden could be reduced by 81% when China’s experience with malaria control was shared in Tanzania through interactions between health officials from China and Tanzania.…”
Section: Discussionmentioning
confidence: 99%